Pengaruh Promosi Digital Dan Kualitas SDM Terhadap Citra Merek Kopi Titik Koma Di Surabaya - Anjeli Brasilia; Nilam Shelly Heniati; Sofiatun Sofiatun; Nindya Kartika Kusmayati (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
With the increasing number of business players in the coffee shop industry, brand image has become a crucial element in shaping customer perception and loyalty. This study aims to analyze the contribution of digital promotion and human resource quality in shaping the brand image of Kopi Titik Koma in Surabaya. Employing a quantitative approach, the research collected data through a survey involving a total of 60 respondents. The data were analyzed using multiple linear regression with SPSS 25. The findings indicate that both variables have a positive and significant influence on brand image, both partially and simultaneously. The regression model obtained is Y = 2.909 + 0.286X1 + 0.538X2 + e, indicating that the quality of human resources contributes more substantially (0.538) compared to digital promotion (0.286). These results highlight the strategic importance of digital efforts and human resource development in enhancing brand image. Future studies are recommended to focus on more specific geographical areas to gain deeper insights.